2011
DOI: 10.1161/circep.110.959809
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Long-Term Prognosis of Vasospastic Angina Patients Who Survived Out-of-Hospital Cardiac Arrest

Abstract: on behalf of the Japanese Coronary Spasm Association Background-Coronary artery spasm plays an important role in the pathogenesis of ischemic heart disease; however, its role in sudden cardiac death remains to be fully elucidated. We examined the clinical characteristics and outcomes of patients with vasospastic angina (VSA) in our nationwide multicenter registry by the Japanese Coronary Spasm Association. September 2007 and December 2008, 1429 patients with VSA (male/female, 1090/339; median, 66 years) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
150
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(164 citation statements)
references
References 41 publications
8
150
0
6
Order By: Relevance
“…Takagi et al showed that the incidence of cardiac death was significantly increased in patients for whom medications were reduced or discontinued 8. As shown in Figure 7A, the incidence of VF recurrence in the CAS group is consistent with that reported in previous studies 8, 21. In the current study (Figure 7B), 3 symptomatic patients with CAS experienced VF recurrence, with 2 of those experiencing VF recurrence after discontinuation of antianginal therapy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Takagi et al showed that the incidence of cardiac death was significantly increased in patients for whom medications were reduced or discontinued 8. As shown in Figure 7A, the incidence of VF recurrence in the CAS group is consistent with that reported in previous studies 8, 21. In the current study (Figure 7B), 3 symptomatic patients with CAS experienced VF recurrence, with 2 of those experiencing VF recurrence after discontinuation of antianginal therapy.…”
Section: Discussionsupporting
confidence: 90%
“…They reported that the annual incidence rate of recurrent ventricular tachyarrhythmia was ≈3% 21. Takagi et al showed that the incidence of cardiac death was significantly increased in patients for whom medications were reduced or discontinued 8. As shown in Figure 7A, the incidence of VF recurrence in the CAS group is consistent with that reported in previous studies 8, 21.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…9 In particular, the indication of ICD for the secondary prevention of lethal VAs because of CAS is controversial because CAS could be effectively suppressed by optical medications with calcium channel blockers (CCBs). [10][11][12][13] In the present study, we, thus, examined the long-term prognosis of patients with OHCA classified based on the results of the dual induction tests for CAS and lethal VAs and evaluated the necessity of ICD by the underlying mechanisms involved.…”
mentioning
confidence: 99%